Damage Evolution and Constitutive Model of Marble under Dynamic Loading - Song Xie; Ziyun Li; Qianghui Song; Peiyong Wang; Kaixi Xue; Dongyan Liu (Geofluids)
Through the application of SHPB (split Hopkinson pressure bar) test, the failure mode and dynamic stress-strain curves of marble samples were obtained. The dynamic constitutive model of marble was established with the fracture mechanical parameters (brittleness index), and the calculated curves were compared with the experimental curves. The evolution characteristic of damage variable D was analyzed. The results show that there are three main stages of marble deformation under dynamic impact load, which are linear elastic deformation stage, crack growth stage, and macroscopic failure stage. The sample shows obvious brittleness in the macroscopic failure stage. It is found that with the increase of strain rate, the degree of damage is getting worse. The stress-strain curves obtained based on the constitutive model are in good agreement with the experimental curves. The damage variable D can theoretically explain the evolution law of macroscopic failure of the sample. To some extent, there is a mechanism inside the rock to regulate the damage development of the rock, and the final failure degree of rock sample depends on △σBC and εb.